A systematic review with meta‐analyses of text message‐delivered behaviour change interventions for weight loss and weight loss maintenance. (11th February 2020) - Skinner, Rebecca; Gonet, Veronica; Currie, Sinéad; Hoddinott, Pat; Dombrowski, Stephan U.
SUMMARY: Short Message Service (SMS)‐delivered behaviour change interventions are frequently used to support weight management. This systematic review examines the effectiveness of SMS‐delivered behaviour change interventions for weight management. Electronic databases were searched for randomised controlled trials (RCTs) comparing SMS‐delivered adult weight management interventions to control groups, published between 1990 and 2018. Weight change was examined using random effects meta‐analyses at intervention cessation and postintervention follow‐up. Subgroup analyses examined intervention duration, SMS frequency, theory use, SMS interactivity, and SMS tailoring. Fifteen studies met inclusion criteria (2705 participants). For weight loss interventions (n = 12, 1977 participants), the mean difference in weight change was −2.28 kg (95% confidence interval [CI] −3.17 to −1.36 kg). No studies reported postintervention follow‐up. For weight loss maintenance interventions (n = 3, 728 participants), the mean difference in weight change was −0.68 kg (95% CI, −1.31 to −0.05 kg), and postintervention follow‐up (n = 2, 498 participants) effects were −0.57 kg (95% CI, −1.67 to 0.53 kg). No subgroup differences were found. SMS‐delivered behaviour change interventions for weight loss led to significant small to moderate weight loss and weight loss maintenance compared with control groups. Evidence on long‐term effects is limited. SMS‐delivered behaviour change interventions are a potentially effective and scalable intervention option for obesity treatment.